Coking-resistant Ce0.8Ni0.2O2-δ internal reforming layer for direct methane solid oxide fuel cells - Zhao, J.; Xu, X.; Li, M.; Zhou, W.; Liu, Shaomin; Zhu, Z. (Pergamon, 2018)
The development of direct methane solid oxide fuel cells (SOFCs) is severely hindered by the deactivation of conventional Ni-based anodes due to carbon fouling. Here, a Ce0.8Ni0.2O2-d(CNO) internal reforming layer is imposed on conventional Ni-Sm0.2Ce0.8O2-x(SDC) anodes for direct methane SOFCs. In CNO, there are two types of Ni species which are segregated NiO dispersed over the CNO and incorporated Ni2+in the ceria lattice, respectively. The Ni2+dopants are stable in wet hydrogen at 650 °C; however, the segregated NiO is reduced into Ni under the same conditions. With the doping of Ni2+into the ceria lattice, surface oxygen vacancies are generated in CNO. For the stability testing in wet methane (~3 mol% H2O in methane) at 650 °C and 0.2 A cm-2, the voltage of the conventional Ni-SDC anode decreases by 43.1% in approximately 26 h, whereas the CNO internal reforming layer operates stably for 40 h. In wet methane at 650 °C, with the addition of the CNO internal reforming layer, the polarization resistance of the Ni-SDC anode reduces by 22.3% from 0.0917 to 0.0712 O cm2, and the maximum current density of it increases from 614 to 664 mW cm-2.